Regional algorithms for remote-sensing estimates of total suspended matter in the Beaufort Sea - Tang, Shilin; Larouche, Pierre; Niemi, Andrea; Michel, Christine (International journal of remote sensing, 2013)
The large and variable riverine inflow to Arctic continental shelves strongly influences their chemical, biological, and optical properties. The Beaufort Sea receives the largest amount of suspended sediments amongst all Arctic shelves, with sediment-laden Mackenzie river waters strongly influencing bio-optical properties on the shelf. Here, we developed two regional algorithms for the estimation of total suspended matter (TSM) concentration using Medium Resolution Imaging Spectrometer (MERIS) spectral bands, based on in situ optical and suspended particulate data collected in the summer during the Canadian Arctic Shelf Exchange Study (CASES) in 2004 and during the Arctic Coastal Ecosystem Study (ACES) in 2010. The band ratio (where Rᵣₛ is remote-sensing reflectance) Rᵣₛ,₅₆₀/Rᵣₛ,₄₉₀ was best correlated with low TSM concentrations (less than 3.0 g m⁻³), while higher TSM concentrations were well correlated to Rᵣₛ,₆₈₁/Rᵣₛ,₅₆₀. An empirical piecewise algorithm is thus proposed with the switch between the ratios being triggered by Rᵣₛ,₆₈₁/Rᵣₛ,₅₆₀ at a threshold value of 0.6. The second algorithm made use of support vector machines (SVMs) as a nonlinear transfer function between TSM concentrations and remote-sensing reflectance ratios Rᵣₛ,₆₈₁/Rᵣₛ,₅₆₀, Rᵣₛ,₆₆₅/Rᵣₛ,₅₆₀, and Rᵣₛ,₅₆₀/Rᵣₛ,₄₉₀. Results show that both algorithms perform better (31% and 25%, respectively) than other published TSM algorithms including the MERIS Case 2 water processor (C2R) neural network algorithm in the study area.